The Dynamics of Land Control in Forest Areas by the Customary Law Community of Nagari Simpang, Pasaman Regency - Kurnia, Adenk; Nugroho, Aristiono; Titik Andari, Dwi Wulan (Marcapada: Jurnal Kebijakan Pertanahan, 2024)
Forests in Indonesia are a vital ecosystem, covering 64% of the country’s total land area, according to data from the Ministry of Environment and Forestry (LHK) released in 2020. Forests serve not only as a source of livelihood but also as a place for meeting the needs of communities, including customary law community (MHA) that have long controlled and utilized forest land prior to the establishment of the nation. One example of a land control conflict in forest areas by MHA occurs in Nagari Simpang Utara. The MHA, led by Datuk Putiah, claims the forest area as ulayat land under Minangkabau customary law. The government, through the Ministry of LHK, has designated this area as state forest land according to Law No. 41 of 1999 on Forestry, reinforced by Minister of Forestry Decree No. 35/Menhut-11/2013. This study aims to identify the dynamics of land control by MHA and find conflict resolution solutions in accordance with applicable regulations. The research method used is qualitative with a descriptive approach. The findings indicate that the recognition and existence of MHA often conflict with government policies, causing friction between indigenous communities and state authorities. In this regard, conflict resolution efforts must consider both sides to achieve a fair and sustainable solution.